2015
DOI: 10.11607/prd.2273
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Laser-Lok Surface on Immediate Functional Loading of Implants in Single-Tooth Replacement: Three-Year Results of a Prospective Randomized Clinical Study on Soft Tissue Response and Esthetics

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 0 publications
2
40
2
5
Order By: Relevance
“…The greater initial bone loss seen in both groups (0‐6 months) could be related to the bone remodeling process initiated after fixture installation . The amount of bone loss correspond the findings of a previous study evaluating immediate loading and the same implant system . The lack of statistically significant difference for MBL between groups seems to indicate that immediate loading in the present study did not affect the MBL in relation to delayed loading during the 1 year of function.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The greater initial bone loss seen in both groups (0‐6 months) could be related to the bone remodeling process initiated after fixture installation . The amount of bone loss correspond the findings of a previous study evaluating immediate loading and the same implant system . The lack of statistically significant difference for MBL between groups seems to indicate that immediate loading in the present study did not affect the MBL in relation to delayed loading during the 1 year of function.…”
Section: Discussionsupporting
confidence: 83%
“…The patient who lost an implant was a smoker, considered to be a risk factor for early implant loss . The survival rate for immediate loading was similar to the ones found in other single‐implant studies …”
Section: Discussionsupporting
confidence: 80%
“…After duplicates were discarded, 63 records remained. Review of the titles and abstracts resulted in 22 articles identified as full‐text articles, and seven were excluded for the following reasons: follow‐up <12 months; 44 , 45 redundant studies; 32 LMS design not only in implant neck; 21 , 46 performed with additional surgeries such as hard 47 or soft tissue 48 augmentation. Finally, 15 eligible articles 21‐31,33‐36 were included in this study.…”
Section: Resultsmentioning
confidence: 99%
“…This kind of attachment is similar to that of a natural tooth, which is indispensable as a barrier against bacterial infection, 16 helping to stabilize peri‐implant soft tissue and diminish MBL 20 . Several clinical studies have found that LMS collars could improve marginal bone preservation 21–36 and reduce probing depth (PD) 22‐25,28‐36 . However, some scholars 27 , 30 have different opinions, stating that there is no significant difference in MBL around an LMS compared with a roughened‐surface.…”
mentioning
confidence: 99%
“…In all studies, soft tissue parameters as BoP and peri‐implant mucosa level were similar for the two types of implants compared. One study reported that more often LASER microtextured implants promoted entire filling of the proximal space than rough collar implants (Guarnieri et al, ). Two studies (Guarnieri et al, ) with 55 implants per treatment arm determined that PPD was statistically lower in LASER microtextured implants after 1 year of service, with a mean difference of 1.31 mm ( N = 2 studies, 95% CI: [1.20, 1.42], p < 0.001).…”
Section: Resultsmentioning
confidence: 99%